A blood-based transcriptomic signature stratifies severe Crohn’s disease and defines potentially targetable therapeutic pathways - Gonsky, Rivkah; Adams, Evan; Potdar, Alka A.; Botwin, Gregory; Biener-Ramanujan, Eva; McGovern, Dermot P. B.; Braun, Jonathan G.; Fleshner, Phillip; Targan, Stephan R. (Frontiers in Gastroenterology, 2023)
Despite advances in medical therapy many patients with Crohn's disease (CD) ultimately require surgery for disease management. Identifying underlying molecular pathways for subgroup stratification is critical for improved prognostics, therapeutics and biomarker discovery. We purified CD3 + T-cells from paired blood and mucosa from 100 CD and 17 non-inflammatory bowel disease (IBD) subjects requiring surgery. Longitudinal samples (n=49) were collected 4-13 months postoperatively. Transcriptional profiling at time of surgery revealed 2 CD subgroups: CD-PBT that clustered tightly with non-IBD subjects and CD-PBmu(cosal) that shifted from peripheral toward a mucosal-like expression profile. CD-PBmu was characterized by differential gene expression, elevated genetic transcriptional risk score (TRS) and a distinct T-cell subset composition associated with perianal-penetrating/stricturing disease, post-surgical recurrence and immunoreactivity to multiple microbial antigens. CD-PBmu subtyping was validated in a CD cohort failing anti-TNF therapy. CD-PBmu, in contrast to CD-PBT, was distinguished by decreased pro-inflammatory cytokine/chemokine and adhesion molecule expression postoperatively. For clinical translation, we identified a CD-PBmu 42-gene classifier associated with a TRS signature, clinical severity markers and underlying protein kinase signaling pathways to identify therapeutic targets. The CD-PBmu signature holds potential for future investigation to improve accuracy in identifying a severe CD-subset who may benefit from early initiation of therapeutics to defined molecular pathways.